In. Vitro cleavage of supercoiled double stranded dna by crude extract of Annona squamosa L.: Pemotongan dna superkoil untai ganda secara in vitro oleh eks7'rak - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1998)
The ability of cleaving, supercoiled double stranded DNA has recently been found in several ribosome-inactivating proteins (RIP), a group of toxic proteins produced in plants, such as: trichosantin from Trichosanthes kirilowil, ricin from Ricinus communis and pokeweed antiviral protein (PAP) from Phytalocca americana. This potent activity makes them excellent candidates as the toxic part of immunotoxin for cancer therapy. The supercoiled DNA cleaving activity was used to identify the presence of RIP in Annona squamosa, a plant which has been traditionally used to prevent pregnancy. Results showed that the crude extract of A.squamosa seeds expressed enzymatic activity to cleave supercoiled double stranded DNA into a nick circular conformation at low concentrations. Incubation at high concentration indicated that supercoiled DNA was cleaved into a linear form. However, it had no effect on a linear DNA. It can be concluded that A. squamosa seeds contains RIP-like protein. Key word : Ribosome-inactivating protein (RIP), Annona squamosa L. ABSTRAK Kemampuan untuk memotong DNA superkoil untai ganda secara in-vitro akhir-akhir ini diketahui dimilild oleh beberapa ribosome-inactivating protein (RIP), yakni sekelompok protein toksik yang dihasilkan Â°felt beberapa tanaman, seperti: trichosantin yang berasal dad tanaman Trichosanthes kirilowii, ricin dari Ricinus communis dan pokeweed antiviral protein (PAP) dad Phytalocca americana. Aktivitas ini Akan dapat menjadikan RIP sebagai ujung toksik dari suatu immunotoksin untuk pengobatan penyakit kanker Aktivitas memotong DNA superkoil ini digunakan untuk menguji adanya kandungan RIP dalam Annona squamosa, yakni tanaman yang secara tradisional telah digunakan sebagai pencegah kehantilan.